Outcome of audiometric masking therapy on subjective tinnitus patients in different age groups - Mohanty, Prabina Rashmi; Walikar, Basavaraj N.; Rashinkar, Satish M.; Kakeri, Ashfak R.; Watwe, Milind V.; Biradar, Wasifa S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Theoretical consideration suggests an impact of the age at tinnitus onset influencing tinnitus distress. The use of masking for tinnitus is a primary method of treatment of tinnitus. The objective was to study effectiveness of masking by introducing audiometric reference signal in treatment of subjective tinnitus. Methods: The 90 patients (45 males and 45 females) were assessed by pure tone audiometer. Patients were divided into 6 age group sets for evaluation. The reference signal (90 to 100 dB SPL for 2-3 minutes in tinnitus ear of frequency 1000 Hz) was used for masking therapy. Outcome of the study was measured by using the tinnitus handicap inventory (THI) score and awareness time (tinnitus perception) before and after audiometric reference signal masking therapy. Success rate was measured to measure therapeutic efficacy. Results: Our results depict improvement in subjective tinnitus by 57.78% (in males), 55.56% (in females) and overall 56.67% success in patients aged between 21 to 60 years by using our audiometric reference signal masking therapy. Regarding gender, the finding of THI score, Awareness time and Success rate in our study showed females being affected more than males. Our study also evidenced a highest percentage of tinnitus after the age of 70 followed by the decades 61–70 and 51–60. Conclusions: Our new economically viable approach to subjective tinnitus patients by audiometric reference signal seems to be an effective in improving the patient’s distress in age group 21 to 60 years. Before taking decision for selection of high cost hearing aids, we can use it for poor people.